The effect of methylation on the wogonin’s in vitro and in silico antidiabetic activity - Sarian, Murni Nazira; Ahmed, Qamar Uddin; Alhassan, Alhassan Muhammad; Latip, Jalifah (2018)
Wogonin is one of the flavonoids that has been reported to exert antihyperglycemic effect against type 2 diabetes mellitus. However, the structure activity relationships (SAR) studies of wogonin against this disease have not been carried out. Hence, the objective of this study was to determine the effect of methylation on wogonin and some structurally related flavonoids to recognize important positions responsible and their correlation. 13 chemical analogues of wogonin were selected and subjected to cytotoxicity test (MTT) on two different cell lines namely RIN-5F pancreatic and 3T3-L1 pre-adipocytes. Subsequently, the compounds were subjected to in vitro antidiabetic investigation using RIN-5F to determine the insulin secretagogue activity via ELISA as well as on 3T3-L1 adipocytes to determine the insulin sensitizing activity via adipogenesis and fluorescence glucose uptake tests. Next, the adipokines viz. leptin, tumor necrosis factor-α (TNF-α), adiponectin, and retinol binding protein-4 (RBP-4) were measured to investigate the biochemical reactions. Afterward, western blotting was performed to check GLUT4 and C-EBPα protein expressions. To further understand the mechanism, molecular docking study against GLUT1 receptor was executed. Results of in vitro antidiabetic (insulin secretion, adipogenesis, glucose uptake), and protein expression showed that the methyl ether group at position C-8 is responsible for wogonin’s antidiabetic capacity via glucose uptake and upregulation of GLUT4 and C/EBP-α. The results might prove worthy of developing semi-synthetic analogs that may retain substantial antidiabetic capacity.